Data from: The effect of uncertain bottom friction on estimates of tidal current power - Kreitmair, Monika J.; Draper, Scott; Borthwick, Alistair G.L.; van den Bremer, Ton S. (Dryad, 2018)
Uncertainty affects estimates of the power potential of tidal currents,
resulting in large ranges in values reported for a given site, such as the
Pentland Firth, UK. We examine the role of bottom friction, one of the
most important sources of uncertainty. We do so by using perturbation
methods to find the leading-order effect of bottom friction uncertainty in
theoretical models by Garrett & Cummins (2005), Vennell (2010),
and Garrett & Cummins (2013), which consider quasi-steady flow in
a channel completely spanned by tidal turbines, a similar channel but
retaining the inertial term, and a circular turbine farm in laterally
unconfined flow. We find that bottom friction uncertainty acts to increase
estimates of expected power in a fully-spanned channel, but generally has
the reverse effect in laterally unconfined farms. The optimal number of
turbines, accounting for bottom friction uncertainty, is lower for a
fully-spanned channel and higher in laterally unconfined farms. We
estimate the typical magnitude of bottom friction uncertainty, which
suggests that the effect on estimates of expected power lies in the range
−5 to +30%, but is probably small for deep channels such as the Pentland
Firth (5-10%). In such a channel, the uncertainty in power estimates due
to bottom friction uncertainty remains considerable, and we estimate a
relative standard derivation of 30%, increasing to 50% for small channels.
V10_optimum_RSOSMatlab code used to find the value of turbine drag
parameter which maximises the expected power under uncertain bed roughness
parameter for the model presented in R.A. Vennell, Tuning Tidal Turbines
In-Concert to Maximise Farm Efficiency, J. Fluid Mech., 671:587–604, 2010.
Keywords: Renewable energy; resource assessment; bed roughness; tidal power; tidal currents